Development of a hydrogeological conceptual model for shallow aquifers in the data scarce Upper Blue Nile Basin - Walker, D.; Parkin, G.; Gowing, J.; Haile, Alemseged Tamiru (MDPI, 2019)
Rural communities in sub-Saharan Africa commonly rely on shallow hand-dug wells and springs; consequently, shallow aquifers are an extremely important water source. Increased utilisation of shallow groundwater could help towards achieving multiple sustainable development goals (SDGs) by positively impacting poverty, hunger, and health. However, these shallow aquifers are little studied and poorly understood, partly due to a paucity of existing hydrogeological information in many regions of sub-Saharan Africa. This study develops a hydrogeological conceptual model for Dangila woreda (district) in Northwest Ethiopia, based on extensive field investigations and implementation of a citizen science programme. Geological and water point surveys revealed a thin (3–18 m) weathered volcanic regolith aquifer overlying very low permeability basalt. Hydrochemistry suggested that deep groundwater within fractured and scoriaceous zones of the basalt is not (or is poorly) connected to shallow groundwater. Isotope analysis and well monitoring indicated shallow groundwater flow paths that are not necessarily coincident with surface water flow paths. Characteristics of the prevalent seasonal floodplains are akin to “dambos” that are well-described in literature for Southern Africa. Pumping tests, recharge assessments, and hydrometeorological analysis indicated the regolith aquifer shows potential for increased utilisation. This research is transferrable to the shallow volcanic regolith aquifers that overlie a substantial proportion of Ethiopia and are prevalent throughout the East African Rift and in several areas elsewhere on the continent.